Degradation and Resilience of the Social Function of Macapat Songs in Contemporary Javanese Society: A Sociological Study of Literature and Its Implications for Character Education - Chairunnisa, Aghnia Alivia; Sulanjari, Bambang; Alfiah, Alfiah (Program Studi Pendidikan Bahasa dan Sastra Daerah, 2024)
Macapat songs as Javanese oral literary heritage face serious pressure from social changes accelerated by globalization and digitalization. This study aims to: (1) identify and analyze the degradation process of macapat's social functions in contemporary Javanese society; (2) map resilience strategies of macapat communities in maintaining their relevance; and (3) formulate pedagogical implications for character education based on local wisdom. Employing a literary sociology approach with Ratna's (2012) literary function theory and Bourdieu's (1993) habitus-capital framework, this study applies a qualitative multi-method design combining content analysis of 11 macapat pupuh from Serat Centhini, in-depth interviews with 18 purposive informants (dalang, Javanese linguistics experts, teachers, and cultural activists), and virtual ethnography of online macapat communities. Results indicate that macapat functions have been reduced from five historical functions (entertainment, moral education, protective rituals, life cycle markers, and social cohesion) to two dominant contemporary functions (performance aesthetics and cultural identity), yet significant resilience emerges through digital neo-traditionalism movements. These findings underscore the need for macapat recontextualization in Outcome-Based Education (OBE) curricula as a character education instrument.